2003
DOI: 10.1212/01.wnl.0000040250.31755.f9
|View full text |Cite
|
Sign up to set email alerts
|

Role of C-nociceptive fibers in the nerve axon reflex-related vasodilation in diabetes

Abstract: The nerve axon reflex-related vasodilation is directly related to the function of the C-nociceptive fibers and is significantly associated with other nerve function measurements. As this is an objective measurement, it has the potential to be used as an alternative to currently employed techniques to evaluate small-fiber function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…For our HT measurements, we examined the plantar metatarsal area of the foot and the palm that are covered by glabrous skin that is rich in arteriovenous anastomosis and has increased blood flow. We chose these areas because foot ulcers mainly occur in this type of skin and because previous studies (16,17) have indicated different mechanisms of vasodilation in this area when compared with hairy skin that has considerably less arteriovenous anastomosis. The observed results in glabrous skin areas were similar to HT results we previously observed at the dorsum of the foot and the forearm areas of hairy skin.…”
Section: Discussionmentioning
confidence: 99%
“…For our HT measurements, we examined the plantar metatarsal area of the foot and the palm that are covered by glabrous skin that is rich in arteriovenous anastomosis and has increased blood flow. We chose these areas because foot ulcers mainly occur in this type of skin and because previous studies (16,17) have indicated different mechanisms of vasodilation in this area when compared with hairy skin that has considerably less arteriovenous anastomosis. The observed results in glabrous skin areas were similar to HT results we previously observed at the dorsum of the foot and the forearm areas of hairy skin.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that damage to unmyelinated fibers has a great impact on skin, with disordered blood flow predisposing to foot ulcers (4,38). Some authors have considered small nerve fibers to be the first fibers to be affected in diabetes (39 -41).…”
Section: Discussionmentioning
confidence: 99%
“…This axon mediated response normally accounts for roughly 1/3 of the endothelium-dependent vasodilation in the foot and forearm (Hamdy et al, 2001). This neurogenic vasodilatory response is impaired in the presence of diabetic peripheral neuropathy and the number of sensory neurons for substance P and CGRP reduced (Levy et al;Caselli et al, 2003).…”
Section: Microvascular Factors and Ulcerationmentioning
confidence: 99%